Analysis of Cosmetic Product Names and Innovations in the Modern Cosmetic Industry - Rakhmanova, Nilufar Bakhodirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the Uzbek equivalents of cosmetic product names and innovations in the modern cosmetic industry. The study examines the international names of cosmetic products and their use in Uzbek, highlighting the balance between global marketing strategies and language adaptation. The article examines the historical development of the cosmetic industry from ancient civilizations to the present day, the formation of major brands, and today’s innovations in areas such as AI, environmental friendliness, and personalized care. The study used web sources, industry reports, and works by leading authors in cosmetic science (Perry Romanowski, Nava Dayan, Randy Schueller) as a basis. The results of the article identify important areas for future scientific research on the localization of cosmetic names and environmental sustainability.